Demographic rise of sea urchin Centrostephanus sylviae on Robinson Crusoe and Santa Clara Islands at the Juan Fernandez Archipelago: A biophysical and ecological approach - Valentina Nuñez-Espinosa; Carolina Parada; Braulio Tapia; Billy Ernst; Javier Porobic; David Veliz; Iván Hinojosa; Leonardo Yévenes-Vega (PLoS ONE, 2025)
The large increase in the population of long-spined sea urchins (Centrostephanus sylviae) has gained significant attention in the past decade due to the rise in the number of individuals reported as bycatch in Juan Fernandez rock lobster traps (Jasus frontalis) and the risks associated with changes in the ecosystem structure due to the increase in bleaching of reefs in the Juan Fernandez Archipelago (JFA). We explored the demographic surge of the C. sylviae population on Robinson Crusoe and Santa Clara islands (RC-SC) through changes in the relative abundance of adult sea urchins during the years 2015–2022. To seek an explanation for this phenomenon, we explored the potential contributions of early life stages of sea urchins to the adult population via biophysical modeling. We performed simulations of larval dispersal patterns and connectivity between release and recruitment zones for three study years (2013, 2015, and 2018). The results from larval drift simulations combined with observation data from the crustacean fishery monitoring program helped identify recruitment zones (primarily located in the eastern, southeastern, and southwestern areas of RC-SC). Also, we explored the relationship between the relative abundance of adult sea urchins and traits associated with lobsters due to the predator-prey relationship evident in other ecosystems (i.e., in Tasmania and New Zealand). We explored the potential control by lobsters of the sea urchin population size through generalized linear models by analyzing several predictor variables. The results showed that once all zones were combined there was an inverse correlation between the relative abundance of sea urchins and the largest lobsters found in the traps around the islands. This work highlights the complex ecological dynamics resulting from the increase in the C. sylviae population in the JFA system, emphasizing the importance of addressing this issue through ecosystemic and socio-ecologically integrated approaches.